Public Policies for the Financing of Basic Education: Mapping Research on Fundeb (Research, Society and Development, 2021)
The article aims to analyze the existing academic productions with the Fundeb theme and their contributions to the improvement of the Brazilian educational process. This is a study supported by bibliographical and documentary research that begins with the right to education as a public policy, and continues with the study of the main sources for financing basic education from the 1988 Federal Constitution, followed by the review of literature, whose highlight is the Fund for Maintenance and Development of Basic Education and Valorization of Education Professionals (Fundeb). In this sense, discussions begin with the choice of sources from the Brazilian Digital Library of Theses and Dissertations (BDTD), due to the notoriety of the research meeting of the main universities in the country, on the subject. The productions show us an overview of how Fundeb worked until the year 2020, demonstrating the aspects that should be improved in the New Fundeb. Research shows how Fundeb, throughout its duration, has proven to be essential for financing basic education, even though it needs some adjustments and improvements.